2016
DOI: 10.1136/jnnp-2016-314117
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular therapy for acute ischaemic stroke: the Pragmatic Ischaemic Stroke Thrombectomy Evaluation (PISTE) randomised, controlled trial

Abstract: ObjectiveThe Pragmatic Ischaemic Thrombectomy Evaluation (PISTE) trial was a multicentre, randomised, controlled clinical trial comparing intravenous thrombolysis (IVT) alone with IVT and adjunctive intra-arterial mechanical thrombectomy (MT) in patients who had acute ischaemic stroke with large artery occlusive anterior circulation stroke confirmed on CT angiography (CTA).DesignEligible patients had IVT started within 4.5 hours of stroke symptom onset. Those randomised to additional MT underwent thrombectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
244
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 290 publications
(247 citation statements)
references
References 26 publications
1
244
1
1
Order By: Relevance
“…[11][12][13][14][15][16][17] The average increase in likelihood of good functional outcome at 90 days after IAT is 19.5%. 18 Three studies suggest that high BP is a risk factor for poor outcome and SICH in patients treated with IAT.…”
Section: Strokementioning
confidence: 99%
“…[11][12][13][14][15][16][17] The average increase in likelihood of good functional outcome at 90 days after IAT is 19.5%. 18 Three studies suggest that high BP is a risk factor for poor outcome and SICH in patients treated with IAT.…”
Section: Strokementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Because tPA favors recanalization in large vessel occlusions, 10 preinterventional reperfusion obviating the need for thrombectomy is one important conceivable benefit of the bridging approach. 11 According to a recently published meta-analysis, preinterventional reperfusion occurs in about every tenth patient with an intention to bridge.…”
mentioning
confidence: 99%
“…THERAPY, using the Penumbra aspiration system rather than a retrievable stent, presented in 2015 and published in September 2016 and PISTE, a pragmatic trial conducted in the UK only, have both reported a trend to improved outcome that did not reach statistical significance [22,23]. In an attempt to identify the poorest prognosis patients the THERAPY trial targeted patients with a thrombus length of 8mm or longer but failed to show any significant difference in the primary outcome of functional independnece (mRS 0-2) at 90 days, 38% IAT v 30% IVT groups (p=0.52).…”
Section: Not All Recent Rcts Have Been Positivementioning
confidence: 99%